2014
DOI: 10.1007/s00508-014-0560-2
|View full text |Cite
|
Sign up to set email alerts
|

May mean platelet volume levels be a predictor in the diagnosis of pelvic inflammatory disease?

Abstract: Since the MPV value was significantly decreased in patients with PID, it may serve as an additional and even more valuable marker than leukocyte count in the diagnosis of PID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 17 publications
0
21
1
4
Order By: Relevance
“…by Incebiyik et al [1] with interest. The authors concluded that mean platelet volume (MPV) values were significantly decreased among patients with PID.…”
Section: Dear Editormentioning
confidence: 95%
“…by Incebiyik et al [1] with interest. The authors concluded that mean platelet volume (MPV) values were significantly decreased among patients with PID.…”
Section: Dear Editormentioning
confidence: 95%
“…Torsiyon sonucunda arteriyal kan akımının azalması, ödem ve iskemi meydana gelir 2 . Torsiyonun devam etmesiyle arteriyal obstrüksiyona bağlı olarak dokuda nekroz gelişir 3 . Klinik olarak hastalarda şiddetli olabilen alt karın ağrısı, bulantı-kusma, alt batında hassasiyet, pelvik muayenede ele gelen kitle gibi akut batın tablosu ile kliniğe başvururlar 2,4 .…”
Section: Introductionunclassified
“…Ancak invaziv bir girişim olması; adneksiyal torsiyon açısından şüpheli olan klinik durumlarda liberal olarak kullanılmasını önlemektedir. Bu yüzden adneksiyal torsiyon için spesifik bir belirtece olan ihtiyaç halen devam etmektedir 3,4 .…”
Section: Introductionunclassified
See 2 more Smart Citations